Navigated transcranial magnetic stimulation in neurosurgery - Krieg, Sandro; Picht, Thomas (Springer Nature Switzerland, 2025)
Chapter 1. Basic Principles of Navigated Tms -- Chapter 2. TMS, MEG and fMRI: Comparing and Contrasting three Functional Mapping Techniques -- Chapter 3. Basic and Advanced Intraoperative Neurophysiological Monitoring and Mapping in Supratentorial Brain Tumor Surgery -- Chapter 4. Integration of Functional Data in The Clinical Workflow -- Chapter 5. Safety Issues for The Use Of TMS -- Chapter 6. nTMS Motor Mapping: Basic Principles and Clinical Use -- Chapter 7. nTMS-based DTI Fiber Tracking of Motor Pathways -- Chapter 8. nTMS Motor Mapping for Risk Stratification and Clinical Decision Making Support -- Chapter 9. nTMS Language Mapping: Basic Principles and Clinical Use -- Chapter 10. Combining nTMS And Tractography for Language Mapping: an Integrated Paradigm for Neurosurgical Planning -- Chapter 11. Risk Stratification by nTMS Language Mapping -- Chapter 12. Mapping of Further Brain Functions -- Chapter 13. nTMS In Pediatrics: Special Issues and Solutions -- Chapter 14. nTMS in Epilepsy: Functional Mapping and Therapeutic Applications -- Chapter 15. Assessment of Chronic Cervical Myelopathy -- Chapter 16. Navigated rTMS for the Treatment Of Pain -- Chapter 17. High-PAS: Paired Associative Stimulation with High-Frequency Peripheral and High-Intensity Central Component in Spinal Cord Injury Rehabilitation -- Chapter 18. Treatment of Paresis -- Chapter 19. Closed-Loop TMS -- Chapter 20. nTMS Depression Therapy -- Chapter 21. Harnessing Advanced Tractography in Neurosurgical Practice -- Chapter 22. Analysis and Creation of Structural Connectomes in Brain Tumour Patients: Methodological Challenges and Potential Solutions -- Chapter 23. Brain Plasticity and Neurosurgery -- Chapter 24. Outlook on The Potential of nTMS in Neurosurgery.